The quest for Cardenio : Shakespeare, Fletcher, Cervantes, and the lost play - Carnegie, David, 1943-; Taylor, Gary (Oxford Univ. Press, 2012)
Bringing together leading scholars, critics, and theatre practitioners, this collection of essays is devoted to 'The History of Cardenio', a play based on Don Quixote and said to have been written by Shakespeare and the young man who was taking his place, John Fletcher.